Ideal phononic charge-two nodal point and long nontrivial surface arcs in Na2Zn2O3 - Yang, Ying (Frontiers in Physics, 2022)
Recently, there has been significant interest in exploring the chiral quasiparticles in phonons, which describe the atomic lattice vibrations in solids. In this work, using first-principle calculation, we select a realistic material Na2Zn2O3 as an example to demonstrate that it is an ideal candidate with charge-two Dirac point phonons and charge-two Weyl point phonons at high-symmetry points A and G, respectively. The phononic charge-two nodal points in Na2Zn2O3 are visible and almost ideal. That is, there are no other phonon bands nearby. Moreover, nontrivial phononic surface arcs span the whole surface Brillouin zone. Such clean and long nontrivial arc-shaped phononic surface states benefit the experimental detection. The current work is hoped to guide the investigations of chiral nodal points in phononic systems.